Geographic variation in the vocalizations of Australian palm cockatoos (Probosciger aterrimus)*. Issue 1 (2nd January 2017) - Keighley, M. V.; Langmore, N. E.; Zdenek, C. N.; Heinsohn, R.
Abstract: Vocal dialects have been well studied in songbirds, but there have been fewer examples from parrots. The Australian population of palm cockatoos ( Probosciger aterrimus aterrimus ) from Cape York Peninsula in far north Queensland has an unusually large vocal repertoire for a parrot. Most calls are made during their unique display ritual, which also includes a variety of postures, gestures and the use of a manufactured sound tool. Here, we quantify the geographic structural variation of contact calls within and between six major populations of palm cockatoos in Australia, as well as the extent to which frequently given call types are shared. We found that palm cockatoos from the east coast (Iron Range National Park) possess unique contact calls and have fewer call types in common with other locations. This may have resulted from their long-term isolation in rainforest habitat refugia. Such variety in vocal traits presents a rare opportunity to investigate the evolutionary forces creating behavioural diversity in wild parrots. This is also a step towards assessing links between behavioural variation and population connectivity, which is important information for determining the conservation status of palm cockatoos.